Critical socio-cultural elements of the intercultural endeavour of english teaching in colombian rural areas (2014)
This article reports a study done with five English language teachers in Colombian rural areas. Questionnaires and interviews were used to see how these teachers understand their professional practice considering the contextual features of their regional workplaces. Amongst the findings, we noticed that these teachers have to mediate between local and global tensions and also deal with socio-cultural matches and mismatches in their labours. It is hoped this work raises awareness of critical socio-cultural factors involved in the teaching of English in rural settings and of the complexity of its intercultural dimension.Este artículo reporta los hallazgos de una exploración sistemática hecha con cinco profesores de inglés en áreas rurales. Se usaron cuestionarios y entrevistas para vislumbrar la forma como ellos entienden su práctica profesional considerando las características contextuales de las regiones donde trabajan. Dentro de los hallazgos notamos que los profesores tienen que mediar entre tensiones globales y locales; además, tienen que enfrentar discordancias y concordancias socioculturales en su labor. Se espera que este trabajo cree conciencia sobre factores críticos socioculturales involucrados en la enseñanza del inglés en zonas rurales y sobre la complejidad de su dimensión intercultural.